2019
DOI: 10.1002/masy.201800168
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Structures in Polymer Model Networks

Abstract: Advances of the past ten years for synthesis, analysis, and modeling of polymer model networks are critically reviewed with a focus on control and analysis of cyclic structures and their impact on network properties. The hetero‐complementary coupling reaction of the tetra‐PEG gel architecture allows only for cyclic structures containing an even number of network strands, which eliminates the formation of several network defects including pending loops. Nuclear magnetic resonance (NMR) can be used to detect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Nevertheless, it is certainly of interest to analyze the impact of statistical fluctuations in composition in case of end-linking reactions because end-linking reactions are the literature standard for gelation studies of model networks. This point is also of relevance for high conversions, as composition fluctuations freeze in during the cross-linking reaction …”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, it is certainly of interest to analyze the impact of statistical fluctuations in composition in case of end-linking reactions because end-linking reactions are the literature standard for gelation studies of model networks. This point is also of relevance for high conversions, as composition fluctuations freeze in during the cross-linking reaction …”
Section: Introductionmentioning
confidence: 87%
“…Recently, Nishi et al 94 report gel point conversions of a copolymerization of 4-functional stars in the inset of their Figure 3, which we have plotted also in Figure 14. This particular type of reaction suppresses loops made of an odd number of elastic strands, 46 and thus, there are no pending loops present in these networks. Nevertheless, there is still a significant delay of the gel point with respect to the ideal gel point at 1/(f − 1).…”
Section: Experimental Gel Point Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the computer simulations can be used to determine the gel point and its suppression, systematically identify and quantify network ”defects” (dangling ends and primary loops such as those in Figure ), and determine network topology including all higher-order loops (section ). , …”
Section: Prediction: Computer Simulationmentioning
confidence: 99%
“…There are viable synthesis strategies to obtain ACNs; however, obtaining networks with defined structures either proves difficult [1] or certain criteria for model networks remain unmet [12,13]. Sakai et al [14] demonstrated a promising pathway to control polymer network structures and minimize network defects.…”
Section: Introductionmentioning
confidence: 99%